On press : the liberal values that shaped the news - Pressman, Matthew, 1981- (Harvard University Press, 2018)
In the 1960s and 70s the American press forged a new set of values. Threatened with obsolescence by the proliferation of new competitors, pressured to rectify their treatment of minorities and women, denounced as biased by both the left and the right, the country's leading news organizations made fundamental changes. They shifted from simply reporting the news to analyzing it. They adopted a more adversarial approach to those in power. They continued to strive for objectivity, but they did so in a way that left many outside their newsrooms (and many on the inside) deeply dissatisfied. In many ways they became more liberal. Powerful institutions like the New York Times and the Los Angeles Times--the two newspapers this book scrutinizes--transformed themselves, with major ramifications for the rest of the news media and for the country as a whole. On Press shows how these changes occurred, why they persisted for three decades after the 1970s, and why the media is reassessing long-held values once again in the Trump era.--